Preparation process of gold tailings rare earth metal synergistic leaching recovery agent
Patent Information
- Application Number
- CN202611247901.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-18
- Publication Date
- 2026-10-13
AI Technical Summary
[0004]本发明的目的在于解决硫酸铁、柠檬酸和硫酸直接混合制备回收剂时,各组分在同一酸度条件下集中作用,易导致产品液相稳定性、柠檬酸利用状态及黄金尾矿稀土浸出效果难以兼顾的问题,提供一种通过两部分柠檬酸顺序加入、两次酸化、第二次分段加酸及原液酸性熟化形成连续控制关系的黄金尾矿稀土金属协同浸出回收剂制备工艺
1、通过在两部分柠檬酸加入之间设置第一次酸化,使两部分柠檬酸在不同酸度条件下参与反应,从而解决直接混合时液相状态难以稳定控制的问题。
Smart Images

Figure CN122898752A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hydrometallurgy and tailings resource utilization technology, specifically to a process for preparing a rare earth metal synergistic leaching and recovery agent for gold tailings. Background Technology
[0002] Gold tailings are one of the main solid wastes generated during gold ore beneficiation. In addition to containing quartz, feldspar, and gangue components such as iron, aluminum, and calcium, they may also contain apatite, monazite-like phosphate mineral phases, and rare earth elements such as lanthanum, cerium, neodymium, and yttrium.
[0003] In existing composite leaching agents containing ferric sulfate, citric acid, and sulfuric acid, the citric acid is typically added to the ferric sulfate solution first, followed by the addition of sulfuric acid to adjust the acidity, or the components are directly mixed. In these methods, all the citric acid comes into contact with ferric iron under similar acidity conditions, making it impossible to control the addition and reaction of citric acid before and after acidification. Furthermore, the simultaneous addition of sulfuric acid can easily cause a rapid increase in local acidity, leading to fluctuations in the concentration of free sulfuric acid and the proportion of free citric acid in different batches of the leaching agent. This, in turn, affects the storage stability of the leaching agent and the leaching effect of rare earth elements in gold tailings. Summary of the Invention
[0004] The purpose of this invention is to solve the problem that when ferric sulfate, citric acid and sulfuric acid are directly mixed to prepare a recovery agent, the concentrated action of each component under the same acidity condition easily leads to difficulties in simultaneously achieving product liquid phase stability, citric acid utilization status and rare earth leaching effect of gold tailings. The invention provides a process for preparing a gold tailings rare earth metal synergistic leaching recovery agent by sequentially adding two parts of citric acid, acidifying twice, adding acid in stages a second time, and aging the original solution in acidity to form a continuous control relationship.
[0005] A process for preparing a rare earth metal co-leaching and recovery agent for gold tailings includes the following steps: Prepare citric acid, ferric sulfate and sulfuric acid, with the molar ratio of the total amount of citric acid to the total amount of ferric iron in ferric sulfate being 0.60:1 to 0.85:1, and divide the citric acid into a first part citric acid and a second part citric acid; Ferrous sulfate is dissolved in water to obtain a ferrous sulfate solution. Without adding sulfuric acid, a first portion of citric acid is added to the ferrous sulfate solution and stirred to react with the ferric iron in the ferrous sulfate to obtain the first reaction solution. Sulfuric acid is added to the first reaction solution for the first acidification until the concentration of free sulfuric acid in the resulting acidified intermediate solution is 0.06 mol / L to 0.16 mol / L. Then, the second part of citric acid is added to the acidified intermediate solution and stirred to obtain the second reaction solution. The remaining sulfuric acid required for the second acidification is added to the second reaction solution in two or three stages, with the amount of sulfuric acid added in the later stage not less than the amount added in the earlier stage, until the concentration of free sulfuric acid in the resulting second acidification solution is 0.15 mol / L to 0.50 mol / L. Without adding water or performing solid-liquid separation, the second acidification solution is acidically matured at 20℃ to 35℃ for 2h to 8h. The matured second acidification solution is filtered, and the main filtrate is collected. The amount of water added is determined according to the total iron concentration of the main filtrate, and the total iron concentration is adjusted to 0.10mol / L to 0.30mol / L to obtain a rare earth metal co-leaching and recovery agent for gold tailings.
[0006] Furthermore, the concentration of ferric iron in the ferric sulfate solution is 0.15 mol / L to 0.35 mol / L; The temperature of the ferric sulfate solution was maintained between 25°C and 40°C. After all the first portion of citric acid was added, the mixture was stirred for 30 to 90 minutes to obtain the first reaction solution.
[0007] Furthermore, the sulfuric acid required for the first acidification is added to the first reaction solution, and the cumulative pumping time of the sulfuric acid is 15 min to 45 min; Continue stirring until the concentration of free sulfuric acid in the resulting acidified intermediate solution is 0.06 mol / L to 0.16 mol / L. Stop adding sulfuric acid and continue stirring for 20 to 60 minutes before adding the second portion of citric acid.
[0008] Furthermore, the temperature of the acidification intermediate solution is maintained at 20°C to 30°C. The second part of citric acid is added to the acidification intermediate solution within 15 min to 45 min. After all the second part of citric acid has been added, the reaction is stirred for another 20 min to 60 min to obtain the second reaction solution.
[0009] Furthermore, the remaining sulfuric acid required for the second acidification is divided into two or three stages, and the sulfuric acid from each stage is added to the second reaction solution in sequence; The amount of sulfuric acid added in the latter stage shall not be less than the amount added in the former stage.
[0010] Furthermore, the cumulative pumping time for each stage of sulfuric acid is 15 to 45 minutes. After the cumulative pumping of each stage of sulfuric acid is completed, an inter-stage acidification equilibration period of 20 to 45 minutes is carried out before adding the next stage of sulfuric acid. After all the remaining sulfuric acid has been added, the concentration of free sulfuric acid in the resulting second acidification solution is 0.15 mol / L to 0.50 mol / L.
[0011] Furthermore, after all the remaining sulfuric acid has been added, the second acidification solution is subjected to acidic aging at 20°C to 35°C for 2 to 8 hours without adding water or performing solid-liquid separation.
[0012] Furthermore, after the acidic curing is completed, the second acidified liquid is filtered and the main filtrate is collected. The amount of water added is determined according to the total iron concentration of the main filtrate, and the total iron concentration is adjusted to 0.10 mol / L to 0.30 mol / L to obtain a rare earth metal co-leaching and recovery agent for gold tailings. In the rare earth metal co-leaching recovery agent for gold tailings, free citric acid accounts for 15% to 35% of the total citric acid.
[0013] Furthermore, samples were taken from the rare earth metal co-leaching recovery agent of gold tailings as response samples. Potassium dihydrogen phosphate was added to the response samples according to the molar ratio of phosphorus to total iron in the response samples of 0.20:1 to 0.40:1. The mixture was then mixed at 20°C to 35°C for 20 min to 60 min, followed by solid-liquid separation. After solid-liquid separation, the proportion of free citric acid in the resulting liquid phase increased by 8 to 25 percentage points compared to the proportion of free citric acid before the addition of potassium dihydrogen phosphate. The proportion of free citric acid is the ratio of the amount of free citric acid to the total amount of citric acid.
[0014] In this invention, the first acidification is set after the first part of the citric acid reaction is completed and before the second part of the citric acid is added, so that the two parts of citric acid enter the iron-containing liquid phase under different free acidity conditions. Then, the final free sulfuric acid concentration is gradually reached through the second stage of acidification, and the original composition of the second acidification liquid is maintained before aging, so that the feeding sequence, acidification endpoint and aging conditions form an interconnected preparation relationship.
[0015] The beneficial effects of this invention are as follows: 1. By setting a first acidification between the addition of two parts of citric acid, the two parts of citric acid participate in the reaction under different acidity conditions, thereby solving the problem of the difficulty in controlling the stable liquid phase state when directly mixed.
[0016] 2. By gradually adding sulfuric acid in stages for the second acidification and performing acidic aging without adding water or performing solid-liquid separation, the second acidification solution gradually reaches the target acidity and maintains its original composition, thereby solving the problem of sudden changes in local acidity and unstable aging state caused by concentrated acid addition.
[0017] 3. By using the concentration of free sulfuric acid as the control endpoint for two acidification processes, and by performing filtration and adjusting the total iron concentration after aging, each preparation step has a clear operational basis, thereby improving the consistency of the recovery agent preparation and its applicability to different gold tailings. Attached Figure Description
[0018] Figure 1 This is a process flow diagram for preparing the rare earth metal synergistic leaching and recovery agent for gold tailings according to the present invention. Figure 2 This is a schematic diagram illustrating the relationship between the addition of two portions of citric acid and the two acidification processes in this invention; Figure 3 This is a flowchart of the acidic ripening and post-treatment process of the original solution in this invention. Figure 4 This is a flowchart illustrating the key control points in the preparation of the recovery agent for this invention. Detailed Implementation
[0019] The present invention will be further described below with reference to specific embodiments. These embodiments illustrate the preparation process, process conditions, detection methods, and effects of the gold tailings rare earth metal synergistic leaching recovery agent of the present invention, and do not constitute a limitation on the scope of protection of the present invention. Without changing the defined raw materials, feeding sequence, acidification process, and maturation process, those skilled in the art can adjust the batch feed amount proportionally according to the reaction equipment volume, raw material purity, and gold tailings composition.
[0020] The gold tailings referred to in this invention are tailings formed during the gold beneficiation process after gravity separation, flotation, cyanidation, or a combination of beneficiation treatments. The recovery agent of this invention is used to leach associated rare earth elements from gold tailings. These rare earth elements include lanthanum, cerium, praseodymium, neodymium, yttrium, and other rare earth elements that can be released from the tailings ore phase under acidic conditions.
[0021] In the following examples, the citric acid used was anhydrous citric acid with a mass fraction of not less than 99.5%, the ferric sulfate was anhydrous ferric sulfate with a mass fraction of not less than 98.0%, and the sulfuric acid was concentrated sulfuric acid with a mass fraction of 98.0%. Before use, the concentrated sulfuric acid was slowly added to deionized water to prepare a 4.000 mol / L sulfuric acid solution. After cooling to room temperature, the solution was standardized using a sodium hydroxide standard solution. When preparing the sulfuric acid solution, the concentrated sulfuric acid was added to the water first, avoiding the direct addition of water to the concentrated sulfuric acid.
[0022] The following examples all use glass reactors equipped with jackets, PTFE stirrers, temperature sensors, metering pumps, and sampling ports. Unless otherwise specified, citric acid and sulfuric acid solutions are continuously added using metering pumps, and temperature fluctuations during the reaction process are controlled within ±1°C of the set value.
[0023] The free citric acid ratio, as referred to in this invention, is the percentage of free citric acid relative to the total amount of citric acid, measured under specified testing conditions. The free citric acid ratio is used for performance evaluation of the recovered agent after preparation and is not used as a real-time control parameter during the first or second acidification process.
[0024] Free citric acid was determined by anion exchange liquid chromatography. Before detection, the peak regions of free citric acid and the iron-citric acid bound component were determined using citric acid standard solution and iron-citric acid standard solution, respectively. The test solution was then subjected to chromatographic separation, and the amount of free citric acid was calculated based on the peak area of free citric acid.
[0025] Take another sample from the same batch of test solution, add ethylenediaminetetraacetic acid (EDTA) to decompose the iron-citric acid binding group, and then determine the total amount of citric acid under the same chromatographic conditions. The ratio of the amount of free citric acid to the total amount of citric acid is the free citric acid ratio.
[0026] In the preparation process of this invention, the concentration of ferric iron and the concentration of free sulfuric acid after the first and second acidifications are used to determine whether the corresponding preparation steps meet the specified conditions; the proportion of free citric acid is used to detect and evaluate the gold tailings rare earth metal co-leaching recovery agent after preparation. Therefore, it is not necessary to continuously measure the proportion of free citric acid during the preparation process; it is only measured after the recovery agent is prepared and when comparison is required in the potassium dihydrogen phosphate response test.
[0027] The free citric acid ratio referred to in this invention is the percentage of citric acid that does not form a common chromatographic peak with iron to the total amount of citric acid. During the determination, take 0.20 mL of the test solution, immediately dilute it 20 times with a diluent having the same free sulfuric acid concentration as the test solution, and inject the sample within 10 minutes of sampling.
[0028] Samples were separated using strong anion exchange liquid chromatography (HPLC). The column size was 4.0 mm × 250 mm, the column temperature was 25 °C, the mobile phase was ammonium nitrate aqueous solution, and the flow rate was 0.80 mL / min. The ammonium nitrate concentration was gradually increased from 5 mmol / L to 80 mmol / L over 20 min. The chromatographic eluent was split into two streams: one stream was sent to a UV detector to detect citric acid at 210 nm, and the other stream was sent to an inductively coupled plasma mass spectrometer (ICP-MS) to detect iron. Before each batch of analysis, citric acid and iron standard solutions were injected separately. The time delay of the two detection signals was corrected. Peaks with a retention time difference of no more than 0.10 min after correction were considered the corresponding peaks. Iron signal peaks with a peak height less than three times the baseline noise were considered as not detecting the corresponding iron signal. Chromatographic peaks with citric acid signals but no detectable corresponding iron signals were counted as free citric acid. An external standard curve for citric acid was established using at least five concentration points, with a correlation coefficient of no less than 0.999.
[0029] To determine the total amount of citric acid, take an equal volume of the test solution and add ethylenediaminetetraacetic acid (EDTA) at a molar ratio of 10:1 to total iron. Maintain the solution at 60°C for 30 minutes to allow the iron-citric acid complex to dissociate. Then, determine the total amount of citric acid under the aforementioned chromatographic conditions. The proportion of free citric acid is equal to the amount of free citric acid divided by the amount of total citric acid, multiplied by 100%.
[0030] In the following examples, the total iron concentration was determined by inductively coupled plasma atomic emission spectrometry (ICP-AES), and the rare earth element content in the gold tailings was determined by microwave digestion and ICP-AES mass spectrometry (MS / MS). The total rare earth leaching rate was equal to the mass of rare earth elements in the gold tailings before leaching minus the mass of the coarse leaching residue obtained by centrifugation and the mass of the remaining rare earth elements in the secondary solid phase obtained by membrane filtration, then divided by the mass of rare earth elements in the gold tailings before leaching and multiplied by 100%. The apparent iron leaching rate from the tailings source in the table was deducted using a blank solution without tailings under the same conditions. The total iron mass in the leaching solution of the experimental group and the blank solution without tailings was first measured separately, then the difference was divided by the iron mass in the gold tailings before leaching and multiplied by 100%. The aluminum leaching rate and calcium leaching rate were calculated based on the same initial mass and the remaining mass after leaching relationship.
[0031] The rare earth entrainment ratio in the secondary solid phase refers to the percentage of rare earth mass contained in the secondary solid phase formed during the leaching process relative to the total rare earth mass released from the gold tailings. After leaching, the sample is centrifuged at a relative centrifugal force of 5000g for 10 minutes. The centrifuged sediment is used as coarse leaching residue. The resulting supernatant is immediately passed through an acid-resistant filter membrane with a pore size of 0.45μm. The fine solids retained on the membrane surface are used as the secondary solid phase. The coarse leaching residue and the secondary solid phase are microwave digested separately, and the rare earth mass is measured. The rare earth mass released from the gold tailings is calculated by subtracting the remaining rare earth mass in the coarse leaching residue from the rare earth mass before leaching. The rare earth mass in the secondary solid phase is divided by the aforementioned release amount and multiplied by 100% to obtain the rare earth entrainment ratio in the secondary solid phase.
[0032] The 7-day precipitation amount was determined under uniform storage and weighing conditions. 100.0 mL of the test reagent was placed in an acid-resistant glass bottle with a nominal volume of 120 mL, sealed, and allowed to stand at 25℃±1℃ for 7 days. All liquid and precipitate in the bottle were passed through a pre-weighed 0.45 μm polytetrafluoroethylene filter membrane. The bottle wall and filter membrane were rinsed with 5.0 mL of washing solution with the same concentration of free sulfuric acid as the test reagent. The filter membrane was dried at 60℃ until the difference in weight between two consecutive weighings 2 hours apart was no greater than 0.5 mg. The 7-day precipitation amount was calculated by dividing the filter membrane weight gain by the sample volume. Three independent samples were prepared for each batch, and the average value and standard deviation were reported.
[0033] The control of ferric iron concentration in ferric sulfate solution is based on the measured ferric iron content of the ferric sulfate raw material and the target solution volume. During preparation, first calculate the feed amount based on the measured ferric iron mass fraction of the ferric sulfate raw material. Add the ferric sulfate to the predetermined amount of water and stir until no undissolved particles are visible to the naked eye after continuous stirring for 10 minutes. Then add water to the calculated volume and measure the ferric iron concentration. If the measured ferric iron concentration is higher than the target value, add water according to material balance. If the measured ferric iron concentration deviates from the target value but is still between 0.15 mol / L and 0.35 mol / L, the subsequent material dosage can be recalculated based on the measured concentration. If the measured ferric iron concentration is lower than 0.15 mol / L or higher than 0.35 mol / L, the ferric sulfate solution should be re-prepared or adjusted before adding the first portion of citric acid; do not add ferric sulfate after the first reaction begins.
[0034] The distribution of the first and second portions of citric acid was based on the homogeneity of the first reaction solution and the stable state after the addition of the second portion of citric acid. When setting the batch, the first portion of citric acid accounted for 64% of the total citric acid as the starting point for the small-scale test, and three distribution groups were set up: 60%, 64%, and 68%. The first stage reaction was carried out under the same ferric iron concentration, total citric acid dosage, and stirring conditions. The distribution group with no continuous sedimentation, low turbidity, and where the speckled suspensions disappeared during continued stirring after the addition of the second portion of citric acid was selected as the distribution ratio for that batch; Examples 1 to 3 used 64%, 60%, and 68%, respectively.
[0035] The first acidification was performed after the first citric acid reaction was completed and before the second citric acid was added. This was to create a difference in free acidity between the first and second citric acid additions. The endpoint was controlled during the first acidification by a combination of sequential acid addition, stirring, and sampling. When the concentration was below 0.06 mol / L, sulfuric acid was added again; when the concentration reached 0.06 mol / L to 0.16 mol / L, sulfuric acid addition was stopped and stirring continued for 20 to 60 minutes; when the concentration exceeded 0.16 mol / L, the batch of acidified intermediate solution was marked as exceeding the limit and prepared again. Endpoint adjustment was achieved by preparing the acidified intermediate solution again, avoiding changes to the system composition by adding water or prematurely adding the second citric acid. Comparative experiments showed that when the free sulfuric acid concentration was below 0.06 mol / L, the acidity difference between the two citric acid addition stages was insufficient; when it was above 0.16 mol / L, the turbidity, amount of stored precipitate, and amount of impurity leaching increased after the addition of the second citric acid.
[0036] The control endpoint for the second acidification process is 0.15 mol / L to 0.50 mol / L. The cumulative pumping time for each stage of sulfuric acid, as referred to in this invention, means the total time the metering pump actually delivers the sulfuric acid for that stage. The stirring, sampling, and testing time required for endpoint adjustment within each stage is not included in the cumulative pumping time. In practice, the amount of sulfuric acid used is first estimated based on the small-scale calibration results of the same batch of raw materials. The expected usage is divided into two to three stages, with a final stage reserved for endpoint adjustment. For the final stage, 80% to 90% of the expected usage is added first, stirred for 20 minutes, and then sampled for testing. Sulfuric acid is then added in increments of 0.25 mL to 0.50 mL, stirred for 20 minutes after each addition, and the free sulfuric acid concentration is measured. Acid addition is stopped once the target range is reached. The amount of sulfuric acid added in the final stage is the sum of all additions within that stage, and this sum is not less than the amount added in the previous stage. If the detected value is below 0.15 mol / L, continue adding the last stage of sulfuric acid. If the detected value exceeds 0.50 mol / L, the batch of second acidification solution is determined to be an acidification over-limit batch and must be prepared again.
[0037] The acidic aging process referred to in this invention refers to maintaining the second acidified solution at 20°C to 35°C and continuously stirring for 2 to 8 hours after the second acidification, without adding water or performing solid-liquid separation. This process eliminates local concentration differences caused by acid addition and stabilizes the liquid phase. During aging, the open feed port is closed and a condenser reflux or equivalent anti-evaporation structure is installed. The stirring speed is set to ensure stable circulation on the liquid surface without significant bubble entrainment; preferably, it is 200 to 350 r / min in a laboratory setting. After aging for 2 hours, the free sulfuric acid concentration and turbidity are measured simultaneously every 30 minutes. Acidic aging is considered complete when the difference in free sulfuric acid concentration between two consecutive measurements is no greater than 0.005 mol / L, the change in turbidity is no greater than 0.3 NTU, and no further increase in particle size is observed. If the aforementioned conditions are met before 2 hours, aging continues for another 2 hours. If the aforementioned completion conditions are not met by 8 hours, the batch of second acidified solution is considered an abnormal aging batch.
[0038] No water is added before acid aging to maintain the total iron concentration, citric acid concentration, free sulfuric acid concentration, and ionic strength at the end of the second acidification. Adding water before aging would simultaneously reduce these concentrations and alter the liquid phase composition formed during the second acidification. Subsequent sulfuric acid addition only changes the free sulfuric acid concentration; the total iron concentration, citric acid concentration, and ionic strength before aging remain at the levels after water addition. No solid-liquid separation is performed before acid aging to retain the fine components in the liquid after the second acidification, allowing them to continue participating in liquid phase state adjustment during the aging process. The comparison results of adding 5% water before aging or pre-filtration are shown in Table 4.
[0039] Filtration after acid curing removes undissolved particles, trace solids formed during acidification and curing, and mechanical impurities. The resulting main filtrate is a continuous liquid phase containing dissolved iron, citric acid, and free sulfuric acid. After filtration, the total iron concentration of the main filtrate is measured first to determine whether water needs to be added. If the total iron concentration of the main filtrate is higher than the target total iron concentration of the product to be obtained, water is added to reduce it to 0.10 mol / L to 0.30 mol / L. If the total iron concentration of the main filtrate is within the range and meets the usage requirements, water does not need to be added. If the total iron concentration of the main filtrate is lower than 0.10 mol / L, and further water addition cannot bring it to the target range, this batch of filtrate is considered an abnormal batch. No water adjustment is made; the concentration of ferric sulfate solution, evaporation control during curing, abnormal precipitation, and filtration loss should be checked, and the filtrate should be prepared again.
[0040] The potassium dihydrogen phosphate response test was used to evaluate the liquid-phase changes of the prepared recovery agent after the introduction of phosphate. During the test, 50.00 mL of the recovery agent was taken as a response sample. The amount of phosphorus used was calculated based on the measured total iron content in the response sample. The mixture was stirred at 20°C to 35°C for 20 to 60 minutes to ensure sufficient contact between the phosphate and iron-containing components, followed immediately by centrifugation and membrane filtration. Solid-liquid separation was used to terminate the continuous contact between the phosphate and the liquid phase, remove phosphorus-containing fine solid phases, and reduce the impact of particle scattering, particle-borne citric acid, and continued reaction on the detection of free citric acid in the liquid phase.
[0041] An increase of 8 to 25 percentage points in the free citric acid ratio is the product response judgment range obtained according to the specified phosphorus-iron ratio, temperature, mixing time, and solid-liquid separation conditions. An increase of less than 8 percentage points indicates insufficient phosphate response from the recovered agent; an increase exceeding 25 percentage points is usually accompanied by an increase in solid phase formation and the proportion of iron transferred into the solid phase, as well as a decrease in test repeatability. Product performance should be evaluated jointly based on the increase in the free citric acid ratio, the amount of solid phase formed, the proportion of iron transferred into the solid phase, and test repeatability. When the test results are within the range of 8 to 25 percentage points, the batch of product is considered to meet the response index. When the test results exceed this range, the batch of product is recorded as a batch exceeding the response index limit and should be re-prepared according to the original process parameters.
[0042] Example 1 This embodiment uses phosphorus-containing rare earth gold flotation tailings with common acid consumption and iron, aluminum, and calcium content as the application material. Analysis revealed that the gold tailings contained 47.1% silica, 13.0% alumina, 8.9% ferric oxide, 11.2% calcium oxide, 2.21% phosphorus pentoxide, and a total rare earth element content of 548 mg / kg. Specifically, the rare earth elements included 96 mg / kg lanthanum, 181 mg / kg cerium, 114 mg / kg neodymium, 87 mg / kg yttrium, and 70 mg / kg of other rare earth elements. The gold tailings were dried to constant weight at 60°C and then ground until over 90% of the particles were smaller than 74 μm.
[0043] Weigh out 20.40 g of anhydrous ferric sulfate. Based on a ferric sulfate mass fraction of 98.0%, the actual amount of ferric sulfate is 0.0500 mol, corresponding to an amount of ferric iron of 0.1000 mol.
[0044] Based on the molar ratio of total citric acid to total ferric iron of 0.72:1, the total amount of citric acid is determined to be 0.0720 mol. Based on the molar mass of anhydrous citric acid of 192.12 g / mol and a mass fraction of 99.5%, 13.90 g of anhydrous citric acid is weighed.
[0045] 13.90g of anhydrous citric acid was divided into two parts: Part I (8.90g, 64.0% of the total citric acid) and Part II (5.00g). Part I was added to deionized water and brought to a final volume of 40.0mL, then stirred until completely dissolved. Part II was added to deionized water and brought to a final volume of 25.0mL, then stirred until completely dissolved.
[0046] Approximately 320 mL of deionized water was added to a jacketed glass reactor with an effective volume of 1 L. Stirring was started, and 20.40 g of anhydrous ferric sulfate was added to the deionized water in four portions, with a 5-minute interval between each addition. After all the ferric sulfate had been added, the temperature was adjusted to 35 °C, and stirring continued for 20 minutes until no undissolved particles were visible to the naked eye. Then, more deionized water was added to bring the volume of the ferric sulfate solution to 400.0 mL. The concentration of ferric iron in the resulting ferric sulfate solution was determined to be 0.250 mol / L.
[0047] The temperature of the ferric sulfate solution was adjusted to 32℃, and the stirring speed was adjusted to 350 r / min. Without adding sulfuric acid, 40.0 mL of the first portion of citric acid solution was continuously added to the ferric sulfate solution using a metering pump over 35 min, with an average addition rate of 1.14 mL / min. After all the first portion of citric acid solution had been added, stirring continued for 60 min at 32℃ and 350 r / min to obtain the first reaction solution. The resulting first reaction solution was brownish-yellow and transparent, with no visible flocculent precipitate observed, and a turbidity of 2.5 NTU.
[0048] Maintain the temperature of the first reaction solution at 32℃, and continuously add 4.000 mol / L sulfuric acid solution to the first reaction solution using a metering pump. For the first 20 minutes after the sulfuric acid solution is added, the addition rate is 0.45 mL / min; after a cumulative addition of 9.0 mL, a sample is taken every time 0.50 mL of sulfuric acid solution is added to determine the free sulfuric acid concentration.
[0049] When a total of 15.2 mL of sulfuric acid solution was added, the concentration of free sulfuric acid in the resulting acidified intermediate solution was 0.103 mol / L, at which point the addition of sulfuric acid was stopped. The total addition time of the sulfuric acid solution was 30 min. After stopping the addition of sulfuric acid, the mixture was stirred for another 40 min at 32 °C and 350 r / min. Samples were taken twice at 10-min intervals, and the concentrations of free sulfuric acid were measured to be 0.103 mol / L and 0.101 mol / L, respectively, yielding the acidified intermediate solution.
[0050] The temperature of the acidification intermediate solution was lowered to 25°C. After the temperature stabilized for 10 minutes, 25.0 mL of the second portion of citric acid solution was continuously added to the acidification intermediate solution using a metering pump over a period of 30 minutes, with an average addition rate of 0.83 mL / min. After all the second portion of citric acid solution had been added, the mixture was stirred for another 45 minutes at 25°C and 350 rpm to obtain the second reaction solution.
[0051] Within the first 5 minutes after the addition of the citric acid solution in the second part, a small amount of speckled suspended matter appeared in the second reaction solution. After stirring for about 7 minutes, the speckled suspended matter disappeared, and no solid was formed that continued to settle. The resulting second reaction solution was a dark brownish-yellow transparent liquid with a turbidity of 3.2 NTU.
[0052] Based on the preliminary test results of the same batch of raw materials, the expected volume of 4.000 mol / L sulfuric acid solution for the second acidification was determined to be 32.0 mL, divided into three stages: 8.0 mL for the first stage, 10.5 mL for the second stage, and 13.5 mL for the third stage. The expected volume of the third stage was greater than that of the previous stage. The third stage served as the endpoint adjustment stage, and its cumulative addition was determined based on the detection results of the free sulfuric acid concentration.
[0053] The temperature of the second reaction solution was adjusted to 28℃, and the stirring speed was maintained at 350 r / min. The cumulative pumping time for the first stage of sulfuric acid solution was 18 min, and stirring continued for 30 min after pumping was completed. The cumulative pumping time for the second stage of sulfuric acid solution was 24 min, and stirring continued for 30 min after pumping was completed. For the third stage, 11.5 mL of sulfuric acid solution was added within the 24-min cumulative pumping time, stirred for 20 min, and then sampled for testing. The endpoint was then adjusted by adding 0.50 mL each time, stirring for 20 min after each addition, and then testing the free sulfuric acid concentration. The cumulative pumping time for the third stage of sulfuric acid solution was 30 min, and the stirring, sampling, and testing time within this stage were not included in the cumulative pumping time.
[0054] When 13.5 mL of sulfuric acid solution was added in the third stage, the concentration of free sulfuric acid in the resulting second acidification solution was measured to be 0.318 mol / L, which reached the control range of 0.15 mol / L to 0.50 mol / L, at which point the addition of sulfuric acid was stopped. During the second acidification, no continuously adhering deposits appeared on the inner wall of the reactor, no large visible flocculants formed in the second acidification solution, and the turbidity of the second acidification solution was 3.6 NTU.
[0055] After the second acidification is completed, no water is added to the second acidified solution, and the solution is not filtered, centrifuged, or allowed to settle and separate. The open feed port of the reactor is closed, and the reactor is connected to the reflux condenser. The second acidified solution is maintained at 28°C and stirred at 250 rpm for 5 hours for acid ripening. After acid ripening continues for 2 hours, the process turbidity is recorded every hour. From 4 hours onwards, the free sulfuric acid concentration and turbidity are simultaneously measured every 30 minutes, and the particle state is observed.
[0056] After 2 hours of acidic aging, the turbidity of the second acidified solution was 2.9 NTU, and after 4 hours of acidic aging, the turbidity was 2.3 NTU. Samples were taken at 4.5 hours and 5 hours of acidic aging, and the free sulfuric acid concentrations were measured to be 0.316 mol / L and 0.317 mol / L, respectively, with turbidities of 2.2 NTU and 2.1 NTU. The difference in free sulfuric acid concentration between the two measurements was 0.001 mol / L, and the difference in turbidity was 0.1 NTU. No further increase in particle size was observed, therefore, the acidic aging was considered complete. The total iron concentration of the resulting acidified second acidified solution was 0.198 mol / L.
[0057] After acid curing, the second acidification solution was cooled to 25°C and filtered using a 0.45 μm PTFE acid-resistant membrane, with the filtration pressure differential controlled between 0.04 MPa and 0.06 MPa. The filter tubing and receiving container were rinsed with the initial 5.0 mL of filtrate, and this portion was then added to the main filtrate, resulting in a final collection of 495.0 mL of main filtrate. The filtration residues included undissolved particles, trace amounts of iron-containing solids, and mechanical impurities. The main filtrate was a continuous liquid phase containing dissolved iron, citric acid, and free sulfuric acid.
[0058] The total iron concentration in the main filtrate was determined to be 0.196 mol / L. The target total iron concentration for the product was set at 0.175 mol / L. Based on the assumption that the amount of iron in the main filtrate remains constant, the adjusted target volume was 554.4 mL. 59.4 mL of deionized water was added to 495.0 mL of the main filtrate, and the mixture was stirred at 25°C for 20 min to bring the liquid volume to 554.4 mL. The total iron concentration of the obtained liquid was re-measured and found to be 0.175 mol / L, thus yielding the rare earth metal co-leaching and recovery agent for gold tailings.
[0059] In this embodiment, the total iron concentration of the filtered main filtrate is 0.196 mol / L, which is higher than the target total iron concentration of 0.175 mol / L. Therefore, the total iron concentration can be reduced by adding water. In actual preparation, the total iron concentration of the main filtrate should be tested first, and then the amount of water to be added should be determined. When the total iron concentration of the main filtrate is already in the range of 0.10 mol / L to 0.30 mol / L and meets the usage requirements, the amount of water added can be reduced or no water added is necessary. When the total iron concentration of the main filtrate is lower than 0.10 mol / L, continuing to add water will only further reduce the total iron concentration. This batch of filtrate should not be adjusted by adding water, and the cause should be investigated and the batch should be prepared again as an abnormal batch.
[0060] The proportion of free citric acid in the rare earth metal co-leaching recovery agent of the obtained gold tailings was measured to be 24.8%. Take 50.00 mL of recovery agent, in which the amount of total iron is 0.00875 mol. Weigh 0.357 g of potassium dihydrogen phosphate according to the molar ratio of phosphorus to total iron of 0.30:1. Dissolve potassium dihydrogen phosphate in 5.00 mL of deionized water and add it to the recovery agent. Mix at 28℃ and 300 r / min for 40 min. Then centrifuge at a relative centrifugal force of 5000 g for 10 min. Filter the supernatant through a filter membrane with a pore size of 0.45 μm.
[0061] Before the addition of potassium dihydrogen phosphate, the proportion of free citric acid in the recovery agent was 24.8%; after solid-liquid separation, the proportion of free citric acid in the resulting liquid phase was 37.1%, an increase of 12.3 percentage points. The increases obtained from three parallel tests were 12.1, 12.6, and 12.2 percentage points, respectively.
[0062] Centrifugation and membrane filtration were performed immediately after mixing to separate the phosphorus-containing fine solid phase from the liquid phase and terminate the reaction. After solid-liquid separation, the liquid phase was collected within 30 minutes for determination of the free citric acid ratio. Without solid-liquid separation, suspended particles can cause instability in chromatographic injection and cause the apparent free citric acid ratio of the same sample to continue to change with standing time.
[0063] Take 50.00 g of the aforementioned gold tailings, add 125 mL of the recovery agent prepared in Example 1 and 125 mL of deionized water, and leach at 50 °C and 300 r / min for 4 h with stirring. After leaching, centrifuge at a relative centrifugal force of 5000 g for 10 min, and then filter using a filter membrane with a pore size of 0.45 μm. The contents of rare earth elements and impurity elements in the leachate and leaching residue are determined respectively.
[0064] Example 2 This embodiment uses high-calcium, high-acid-consumption phosphorus-containing gold tailings as the application material. Testing revealed that the gold tailings contained 21.4% calcium oxide, 5.7% magnesium oxide, 3.38% phosphorus pentoxide, 7.2% ferric oxide, 9.6% aluminum oxide, and a total rare earth element content of 431 mg / kg. The gold tailings were dried to constant weight at 60°C and then ground until particles with a diameter less than 74 μm accounted for more than 92%.
[0065] In this embodiment, the total amount of ferric iron is 0.1200 mol. Based on a ferric sulfate mass fraction of 98.0%, 24.48 g of anhydrous ferric sulfate is weighed. The molar ratio of total citric acid to total ferric iron is 0.82:1, and the total amount of citric acid is 0.0984 mol. Based on an anhydrous citric acid mass fraction of 99.5%, 19.00 g of anhydrous citric acid is weighed. The anhydrous citric acid is divided into a first part (11.40 g) and a second part (7.60 g), which are then dissolved in deionized water to prepare 45.0 mL and 30.0 mL citric acid solutions, respectively.
[0066] Following the method described in Example 1, 24.48 g of anhydrous ferric sulfate was prepared into a 400.0 mL ferric sulfate solution. The concentration of ferric iron in the ferric sulfate solution was determined to be 0.300 mol / L. The ferric sulfate solution was maintained at 38°C. Without the addition of sulfuric acid, 45.0 mL of the first portion of citric acid solution was added over 40 min using a metering pump. After the first portion of citric acid was completely added, stirring was continued for 80 min to obtain the first reaction solution.
[0067] Over a cumulative pumping time of 40 minutes, 20.0 mL of a 4.000 mol / L sulfuric acid solution was added to the first reaction solution using a metering pump. The addition of sulfuric acid was stopped when the free sulfuric acid concentration in the acidification intermediate solution reached 0.142 mol / L. Stirring continued for 50 minutes after stopping the acid addition. The acidification intermediate solution was maintained at 30°C, and 30.0 mL of a second portion of citric acid solution was added over 45 minutes using a metering pump. After all the solution was added, stirring continued for 60 minutes to obtain the second reaction solution.
[0068] The 4.000 mol / L sulfuric acid solution used for the second acidification was divided into two stages: the first stage consisted of 18.0 mL of sulfuric acid solution, and the expected volume for the second stage was 25.0 mL. The cumulative pumping time for the first stage was 40 min, followed by stirring for another 40 min after pumping. For the second stage, 22.0 mL of sulfuric acid solution was added first, then 0.50 mL was added at a time, stirring for 20 min each time, with the free sulfuric acid concentration monitored for endpoint adjustment. The cumulative pumping time for the second stage was 45 min. When the cumulative volume of the second stage reached 25.0 mL, the free sulfuric acid concentration in the resulting second acidified solution was 0.452 mol / L, at which point the addition of sulfuric acid was stopped.
[0069] After the second acidification, no water was added, and no solid-liquid separation was performed. The second acidified solution was maintained at 30°C and stirred at 250 r / min for 6 hours. At 5.5 h and 6 h of acid aging, the free sulfuric acid concentration was measured to be 0.451 mol / L and 0.452 mol / L, respectively, and the turbidity was 2.4 NTU and 2.3 NTU, respectively. No further particle growth was observed, indicating that the acid aging was complete. The total iron concentration of the resulting aged second acidified solution was 0.224 mol / L. The solution was filtered through a 0.45 μm acid-resistant membrane, and the initial 5.0 mL of filtrate was rinsed and added to the main filtrate. 520.0 mL of the main filtrate was collected, and the total iron concentration was measured to be 0.220 mol / L. 52.0 mL of deionized water was added to the main filtrate to bring the liquid volume to 572.0 mL, and the total iron concentration was re-measured to be 0.200 mol / L, yielding the rare earth metal co-leaching and recovery agent for gold tailings in Example 2.
[0070] The proportion of free citric acid in the recovered agent obtained in Example 2 was measured to be 29.4%. 50.00 mL of the recovered agent was taken as a response sample. 0.476 g of potassium dihydrogen phosphate was weighed according to a phosphorus to total iron molar ratio of 0.35:1. After mixing at 30°C for 50 min and completing solid-liquid separation, the proportion of free citric acid in the resulting liquid phase was 44.6%, an increase of 15.2 percentage points compared to before the addition of potassium dihydrogen phosphate.
[0071] Take 50.00g of gold tailings used in Example 2, add 150mL of the recovery agent prepared in Example 2 and 150mL of deionized water, stir and leach for 5h at 55℃ and 300r / min, and then perform solid-liquid separation and elemental detection according to the method in Example 1.
[0072] This embodiment employs a two-stage secondary acidification process and completes the preparation of the recovery agent and rare earth leaching under the application conditions corresponding to high-calcium and high-acid-consumption gold tailings, in order to verify the feasibility of the two-stage secondary acidification in this application scenario.
[0073] Example 3 This embodiment uses gold tailings with high iron and aluminum content and a large proportion of fine particles as the application object. Testing revealed that the gold tailings contained 17.6% ferric oxide, 18.9% alumina, 6.4% calcium oxide, 1.84% phosphorus pentoxide, and a total rare earth element content of 684 mg / kg. Particles with a diameter less than 38 μm accounted for 67% of the total.
[0074] In this embodiment, the total amount of ferric iron was 0.1050 mol. Based on a ferric sulfate mass fraction of 98.0%, 21.42 g of anhydrous ferric sulfate was weighed. The molar ratio of total citric acid to total ferric iron was 0.64:1, and the total amount of citric acid was 0.0672 mol. Based on an anhydrous citric acid mass fraction of 99.5%, 12.98 g of anhydrous citric acid was weighed. The anhydrous citric acid was divided into a first part (8.83 g) and a second part (4.15 g), and citric acid solutions of 35.0 mL and 20.0 mL were prepared respectively with deionized water.
[0075] Following the method described in Example 1, 21.42 g of anhydrous ferric sulfate was prepared into 300.0 mL of ferric sulfate solution. The concentration of ferric iron in the ferric sulfate solution was determined to be 0.350 mol / L. The ferric sulfate solution was maintained at 26°C. Without the addition of sulfuric acid, 35.0 mL of the first portion of citric acid solution was added over 20 min using a metering pump. After the entire portion was added, stirring was continued for 40 min to obtain the first reaction solution.
[0076] Over a cumulative pumping time of 20 minutes, add 12.0 mL of a 4.000 mol / L sulfuric acid solution to the first reaction solution using a metering pump. Stop adding sulfuric acid when the free sulfuric acid concentration in the acidification intermediate solution reaches 0.081 mol / L. Continue stirring for 25 minutes after stopping the addition of sulfuric acid. Maintain the acidification intermediate solution at 22°C, and add 20.0 mL of the second portion of citric acid solution over 20 minutes using a metering pump. After all the solution has been added, continue stirring for 30 minutes to obtain the second reaction solution.
[0077] The 4.000 mol / L sulfuric acid solution used for the second acidification was divided into three stages, with expected addition volumes of 6.5 mL, 8.0 mL, and 10.0 mL, respectively. The cumulative pumping times for each stage were 15 min, 20 min, and 25 min, respectively, followed by stirring for 20 min after each stage's cumulative pumping. For the third stage, 9.0 mL was added initially, followed by 0.25 mL increments, stirring for 20 min each time, and endpoint adjustments were made by monitoring the free sulfuric acid concentration. When the cumulative addition of the third stage reached 10.0 mL, the free sulfuric acid concentration in the resulting second acidification solution was 0.263 mol / L, at which point sulfuric acid addition was stopped.
[0078] After the second acidification, no water was added, and no solid-liquid separation was performed. The second acidified solution was maintained at 32°C and stirred at 250 r / min for 8 hours. At 7.5 h and 8 h of acid aging, the free sulfuric acid concentrations were measured to be 0.262 mol / L and 0.263 mol / L, respectively, and the turbidity was 2.7 NTU and 2.5 NTU, respectively. No further particle growth was observed, indicating that the acid aging was complete. The total iron concentration of the resulting aged second acidified solution was 0.268 mol / L. The solution was filtered through a 0.45 μm acid-resistant membrane, and the initial 5.0 mL of filtrate was rinsed and added to the main filtrate. 380.0 mL of the main filtrate was collected, and the total iron concentration was measured to be 0.260 mol / L. 31.7 mL of deionized water was added to the main filtrate to bring the liquid volume to 411.7 mL, and the total iron concentration was re-measured to be 0.240 mol / L, yielding the rare earth metal co-leaching and recovery agent for gold tailings in Example 3.
[0079] The proportion of free citric acid in the recovered agent obtained in Example 3 was measured to be 19.6%. 50.00 mL of the recovered agent was taken as a response sample. 0.408 g of potassium dihydrogen phosphate was weighed according to a phosphorus to total iron molar ratio of 0.25:1. After mixing at 25°C for 30 min and completing solid-liquid separation, the proportion of free citric acid in the resulting liquid phase was 30.2%, an increase of 10.6 percentage points compared to before the addition of potassium dihydrogen phosphate.
[0080] Take 50.00g of gold tailings used in Example 3, add 125mL of the recovery agent prepared in Example 3 and 125mL of deionized water, stir and leach for 3h at 45℃ and 280r / min, and then perform solid-liquid separation and elemental detection according to the method of Example 1.
[0081] The gold tailings used in this embodiment have high iron and aluminum content and a large proportion of fine particles. Under the preparation parameters and leaching conditions, the recovery agent can be prepared and used for rare earth leaching. This result is used to verify the feasibility of the preparation path of the present invention in scenarios with strong iron and aluminum competition and fine particle adsorption.
[0082] The test results of the recovered agents obtained from the three examples are shown in Table 1. The data in the table are expressed as the average value ± standard deviation of the results from three independent preparations.
[0083] Table 1: Test Results of the Recovered Agents Obtained in Examples 1 to 3 Adjusted total iron concentration 0.175 mol / L 0.200 mol / L 0.240 mol / L Free sulfuric acid concentration 0.284 mol / L 0.400 mol / L 0.238 mol / L Total concentration of citric acid 0.126 mol / L 0.170 mol / L 0.160 mol / L Free citric acid ratio 24.8%±0.6% 29.4%±0.8% 19.6%±0.5% Turbidity 1.9 NTU ± 0.2 NTU 2.2 NTU ± 0.2 NTU 2.5 NTU ± 0.3 NTU Sedimentation amount after being sealed and placed at 25℃ for 7 days 0.23g / L±0.02g / L 0.27g / L±0.03g / L 0.31g / L±0.03g / L Increase in the proportion of free citric acid after adding potassium dihydrogen phosphate 12.3 ± 0.3 percentage points 15.2 ± 0.5 percentage points 10.6 ± 0.4 percentage points Total iron concentration at the end of acid ripening 0.198 mol / L 0.224 mol / L 0.268 mol / L Total iron concentration of the main filtrate obtained by filtration 0.196 mol / L 0.220 mol / L 0.260 mol / L As shown in Table 1, the three embodiments, using different concentrations of ferric iron, molar ratios of citric acid to ferric iron, endpoints of the first acidification, number of stages of the second acidification, final concentrations of free sulfuric acid, and acidic aging conditions, all yielded a recoverable agent with a free citric acid ratio ranging from 15% to 35%.
[0084] Example 2 employed a two-stage secondary acidification process, while Examples 1 and 3 employed a three-stage secondary acidification process, demonstrating that both two-stage and three-stage secondary acidification methods are feasible. The gold tailings treated in Example 3 had higher iron and aluminum content, resulting in slightly higher turbidity and sedimentation levels in the recovered agent compared to Example 1, but it still maintained a homogeneous liquid phase, reflecting reasonable fluctuations under different application conditions.
[0085] As further shown in Table 1, the total iron concentrations at the end of acidic aging in Examples 1 to 3 were 0.198 mol / L, 0.224 mol / L, and 0.268 mol / L, respectively, and the total iron concentrations of the main filtrates obtained by filtration were 0.196 mol / L, 0.220 mol / L, and 0.260 mol / L, respectively, all of which were not lower than 0.10 mol / L. The initial amount of ferric iron, solution preparation volume, sampling loss, filtration volume, and concentration adjustment amount in each example form a corresponding material balance relationship, and the main filtrate can retain a total iron concentration that meets the requirements for subsequent concentration adjustment.
[0086] The results of the application of gold tailings in Examples 1 to 3 are shown in Table 2.
[0087] Table 2: Application Results of Examples 1 to 3 in Different Gold Tailings Total rare earth element content in gold tailings 548mg / kg 431mg / kg 684mg / kg Total rare earth leaching rate 54.0%±0.7% 50.8%±0.8% 57.6%±0.9% Apparent iron leaching rate from tailings 18.9%±0.6% 16.2%±0.5% 27.4%±0.8% Aluminum leaching rate 12.7%±0.5% 10.9%±0.4% 24.8%±0.7% Calcium leaching rate 28.4%±0.7% 41.8%±1.1% 18.3%±0.6% Secondary solid phase rare earth entrainment ratio 4.6%±0.4% 5.2%±0.4% 6.1%±0.5% As shown in Table 2, the gold tailings used in Example 2 had a high calcium oxide content, and under the corresponding conditions of recoverant dosage, temperature, and time, the total rare earth leaching rate was 50.8%. The gold tailings used in Example 3 had a high iron and aluminum content and a high proportion of fine particles, and under the corresponding application conditions, the total rare earth leaching rate was 57.6%. The apparent iron leaching rates from the tailings in the table have been adjusted to exclude the amount of liquid iron introduced by the recoverant in the blank study without tailings under the same conditions.
[0088] The three embodiments correspond to common phosphorus-containing tailings, high-calcium and high-acid tailings, and high-iron and high-aluminum fine-grained tailings, respectively. The data are used to verify the feasibility of each embodiment in the corresponding application scenarios. The amount of recovery agent, leaching temperature and leaching time used in each group are different. The leaching rate between groups is used for scenario verification and is not directly compared as a single variable.
[0089] The following comparative examples are all based on Example 1. Each comparative example was prepared independently in three batches. Tables 3 and 4 show the average values of the three batches to compare the trends of process changes.
[0090] Comparative Example 1 adjusted the molar ratio of total citric acid to total ferric iron to 0.50:1, which is lower than 0.60:1, while the other conditions were the same as in Example 1.
[0091] Comparative Example 2 adjusted the molar ratio of total citric acid to total ferric iron to 0.95:1, which is higher than 0.85:1, while the other conditions were the same as in Example 1.
[0092] In Comparative Example 3, during the first acidification process, sulfuric acid was stopped when the concentration of free sulfuric acid in the acidification intermediate solution reached 0.040 mol / L, and then a second portion of citric acid was added. The remaining conditions were the same as in Example 1.
[0093] In Comparative Example 4, during the first acidification process, sulfuric acid was stopped when the concentration of free sulfuric acid in the acidification intermediate solution reached 0.200 mol / L, and then a second portion of citric acid was added. The remaining conditions were the same as in Example 1.
[0094] Comparative Example 5: The amount of sulfuric acid added during the second acidification was adjusted so that the concentration of free sulfuric acid in the second acidification solution was 0.100 mol / L, which is lower than 0.15 mol / L. The other conditions were the same as in Example 1.
[0095] Comparative Example 6 adjusted the amount of sulfuric acid added during the second acidification so that the concentration of free sulfuric acid in the second acidification solution was 0.600 mol / L, which is higher than 0.50 mol / L. The other conditions were the same as in Example 1.
[0096] In Comparative Example 7, the 32.0 mL sulfuric acid solution used for the second acidification in Example 1 was continuously added to the second reaction solution over 72 min without segmentation. The total amount of sulfuric acid, the total addition time, and the total stirring time after the addition of sulfuric acid were kept consistent with those in Example 1.
[0097] Comparative Example 8 had its acidic aging time adjusted to 1 hour, while the other conditions remained the same as in Example 1.
[0098] Comparative Example 9 had its acidic aging time adjusted to 10 hours, while the other conditions remained the same as in Example 1.
[0099] After the second acidification was completed, Comparative Example 10 added 5% of the volume of the second acidification liquid with deionized water, and then carried out acidic aging according to the conditions of Example 1.
[0100] After the second acidification, Comparative Example 11 was first filtered using a 0.45 μm acid-resistant filter membrane, and then the resulting filtrate was acidified and aged.
[0101] Comparative Example 12 uses a direct mixing method to prepare the recovery agent. All citric acid is added to the ferric sulfate solution at once, and after stirring for 60 minutes, the same amount of sulfuric acid solution as in Example 1 is continuously added over the same total time. The mixture is then stirred at 28°C until the total treatment time is the same as in Example 1. Finally, the recovery agent is obtained by filtration and concentration adjustment as in Example 1.
[0102] The detection results of Example 1 and Comparative Examples 1 to 6 are shown in Table 3.
[0103] Table 3: Comparison Results of Main Process Scope and Outside Example 1 0.23g / L 24.8% 12.3 percentage points 54.0% 18.9% 12.7% 4.6% Comparative Example 1: Molar ratio 0.50:1 0.48g / L 12.7% 8.4 percentage points 48.9% 16.7% 11.3% 7.2% Comparative Example 2: Molar ratio 0.95:1 0.18g / L 39.2% 5.1 percentage points 54.6% 19.5% 13.3% 4.3% Comparative Example 3: First acidification 0.040 mol / L 0.39g / L 27.6% 8.7 percentage points 50.5% 18.2% 12.3% 6.3% Comparative Example 4: First acidification 0.200 mol / L 0.34g / L 22.1% 8.9 percentage points 51.1% 20.4% 14.1% 5.8% Comparative Example 5: Second acidification 0.100 mol / L 0.28g / L 23.9% 11.4 percentage points 47.8% 12.9% 8.5% 5.2% Comparative Example 6: Second acidification 0.600 mol / L 0.22g / L 24.4% 12.5 percentage points 55.2% 29.8% 21.7% 4.4% As shown in Table 3, when the molar ratio of citric acid to ferric iron is reduced to 0.50:1, the initial free citric acid ratio of the recovered agent is relatively low, but the amount of precipitate after 7 days and the proportion of secondary solid rare earth entrainment increase significantly, and the total rare earth leaching rate decreases. This indicates that too low a citric acid dosage will reduce the stability of the iron-containing system.
[0104] When the molar ratio of citric acid to ferric iron was increased to 0.95:1, the 7-day precipitation of the recovered agent was low, and the total rare earth leaching rate was close to that of Example 1. However, the initial free citric acid ratio reached 39.2%, exceeding 35%, and the increase in the free citric acid ratio after adding potassium dihydrogen phosphate was only 5.1 percentage points. Further increasing the amount of citric acid did not lead to a corresponding increase in the rare earth leaching rate, and at the same time reduced the utilization rate of unit citric acid. Therefore, controlling the molar ratio of citric acid to ferric iron between 0.60:1 and 0.85:1 can balance product stability, citric acid utilization, and rare earth leaching effect.
[0105] When the first acidification endpoint is 0.040 mol / L, the acidity difference experienced during the two citric acid addition stages decreases, leading to an increase in the amount of precipitate and the proportion of secondary solid rare earth entrainment in the recovered agent. When the first acidification endpoint is increased to 0.200 mol / L, the total rare earth leaching rate decreases, while the leaching rates of iron and aluminum increase. Controlling the first acidification endpoint between 0.06 mol / L and 0.16 mol / L is beneficial for forming a suitable acidification intermediate solution before the second citric acid addition.
[0106] When the concentration of free sulfuric acid in the second acidification solution is 0.100 mol / L, the leaching rates of iron and aluminum are low, but the total rare earth leaching rate is only 47.8%, indicating that insufficient final acidity will limit the leaching of phosphorus-containing rare earth mineral phases in gold tailings.
[0107] When the concentration of free sulfuric acid in the second acidifying solution was increased to 0.600 mol / L, the total rare earth leaching rate increased to 55.2%, but the apparent leaching rates of iron and aluminum from tailings increased to 29.8% and 21.7%, respectively, resulting in a significant increase in the impurity load during subsequent rare earth separation. Controlling the concentration of free sulfuric acid in the second acidifying solution between 0.15 mol / L and 0.50 mol / L can balance rare earth leaching rate and impurity leaching control.
[0108] The detection results of Example 1 and Comparative Examples 7 to 12 are shown in Table 4.
[0109] Table 4: Comparison of Key Preparation Steps Example 1 0.23g / L 12.3 percentage points 54.0% 18.9% 4.6% Comparative Example 7: Second acidification with one addition 0.31g / L 9.7 percentage points 52.2% 19.3% 5.4% Comparative Example 8: Acidic ripening for 1 hour 0.35g / L 10.0 percentage points 51.6% 18.8% 5.6% Comparative Example 9: Acidic ripening for 10 hours 0.22g / L 12.4 percentage points 54.1% 19.0% 4.5% Comparative Example 10: Add 5% water before maturation 0.30g / L 10.7 percentage points 52.4% 17.6% 5.1% Comparative Example 11: Filtration before ripening 0.33g / L 10.1 percentage points 51.9% 18.0% 5.5% Comparative Example 12: All raw materials were directly mixed. 0.45g / L 6.2 percentage points 48.7% 17.4% 6.9% Acidic ripening for 2 hours to confirm group 0.29g / L 11.2 percentage points 52.9% 18.8% 5.0% Acidic ripening for 8 hours to confirm group 0.22g / L 12.4 percentage points 54.2% 19.1% 4.5% As shown in Table 4, Comparative Example 7 used a single continuous addition of sulfuric acid required for the second acidification. Although the total amount of sulfuric acid, the total feeding time, and the total stirring time after feeding were the same as in Example 1, the 7-day precipitation of the recovered agent increased, the proportion of free citric acid increased, and the total rare earth leaching rate decreased. This indicates that the second acidification in the second to third stages has an independent contribution to the formation of the liquid phase.
[0110] Comparative Example 8 underwent only 1 hour of acidic aging, resulting in a 7-day precipitate concentration of 0.35 g / L and a total rare earth leaching rate of 51.6%. This indicates that the second acidification solution was not sufficiently stable when the aging time was too short. In the group undergoing 2 hours of acidic aging, the 7-day precipitate concentration decreased to 0.29 g / L, the free citric acid ratio increased by 11.2 percentage points, and the total rare earth leaching rate reached 52.9%, indicating that 2 hours can be considered a feasible lower limit for completing acidic aging.
[0111] The 7-day precipitation amount of the 8-hour acidic aging group was 0.22 g / L, the increase in free citric acid ratio was 12.4 percentage points, and the total rare earth leaching rate was 54.2%, which is close to the product state and performance of Example 1. The 7-day precipitation amount, increase in free citric acid ratio, and total rare earth leaching rate of the 10-hour acidic aging group were close to those of the 8-hour group. Further extending the aging time did not produce a identifiable gain. Therefore, controlling the acidic aging time to 2 to 8 hours can balance the stability of the liquid phase and the preparation cycle.
[0112] In Comparative Example 10, after water was added before aging, the concentrations of free sulfuric acid, total iron, and citric acid in the system decreased simultaneously. The 7-day precipitation of the recovered agent increased, the proportion of free citric acid increased, and the total rare earth leaching rate decreased.
[0113] Comparative Example 11, after filtration before aging, showed higher 7-day precipitation and secondary solid rare earth entrainment ratios in the recovered agent compared to Example 1. This result indicates that retaining the original composition of the second acidification solution before completing acid aging is beneficial for stabilizing the state of the recovered agent.
[0114] Comparative Example 12 used direct mixing of all raw materials, and the total raw material composition of the resulting recoverable agent was the same as in Example 1. However, the precipitate amount reached 0.45 g / L after 7 days, and the proportion of free citric acid increased by only 6.2 percentage points after the addition of potassium dihydrogen phosphate. The total rare earth leaching rate was 48.7%. This result indicates that the continuous preparation process consisting of the first part of citric acid reaction, the first acidification, the second part of citric acid reaction, the second stage of acidification, and acid aging can produce a product state and performance different from that of the direct mixing method.
[0115] To further confirm the phosphorus-iron ratio, temperature, mixing time, and solid-liquid separation conditions in the potassium dihydrogen phosphate response test, the recovered agent obtained in Example 1 was used as the sample. Only one test condition was changed, while the other conditions were the same as in Example 1. The test results are shown in Table 5.
[0116] Table 5: Validation Results of Potassium Dihydrogen Phosphate Response Measurement Conditions Solid-liquid separation was performed at a phosphorus-to-iron ratio of 0.30:1, at 28°C for 40 minutes. 12.3 percentage points 8.6% 2.4% Solid-liquid separation was performed at a phosphorus-to-iron ratio of 0.10:1, at 28°C for 40 minutes. 5.9 percentage points 3.1% 4.8% Solid-liquid separation was performed at a phosphorus-to-iron ratio of 0.50:1, at 28°C for 40 minutes. 26.8 percentage points 24.7% 8.7% Solid-liquid separation was performed at a phosphorus-to-iron ratio of 0.30:1, at 15°C, for 40 minutes. 7.1 percentage points 6.4% 6.9% Solid-liquid separation was performed at a phosphorus-to-iron ratio of 0.30:1, at 40°C for 40 minutes. 25.9 percentage points 22.8% 7.8% Solid-liquid separation was performed at a phosphorus-to-iron ratio of 0.30:1, at 28°C for 10 minutes. 6.8 percentage points 4.9% 7.4% Solid-liquid separation was performed at a phosphorus-to-iron ratio of 0.30:1, at 28°C, for 90 minutes. 24.9 percentage points 20.9% 6.2% Phosphorus to iron ratio 0.30:1, 28℃, 40 min, without solid-liquid separation. 28.3 percentage points (apparent value) Repeatability not met requirements 18.4% As shown in Table 5, when the molar ratio of phosphorus to total iron was 0.10:1, the temperature was 15℃, or the mixing time was 10 min, the increase in the proportion of free citric acid was less than 8 percentage points. This indicates that when the amount of phosphate added, the reaction temperature, or the contact time was insufficient, the increase in the proportion of free citric acid was too low, and the dispersion of the three test results increased.
[0117] When the molar ratio of phosphorus to total iron was increased to 0.50:1 or the temperature was increased to 40℃, the increase in the proportion of free citric acid exceeded 25 percentage points. Simultaneously, the proportion of solid iron in the total iron increased significantly, and the relative standard deviation of the three tests increased. Extending the mixing time to 90 minutes resulted in an increase of nearly 25 percentage points, but continued contact led to an increase in the proportion of solid iron. This indicates that the significant increase obtained beyond the specified conditions was accompanied by an increase in the proportion of solid iron. Product performance should be evaluated jointly based on the increase, the proportion of solid iron, and the repeatability of the test.
[0118] When the suspension without solid-liquid separation was sampled directly after mixing, the results were apparent values, and the relative standard deviation of the three tests reached 18.4%, indicating that the three determinations of the solid iron ratio did not meet the preset repeatability requirements. Therefore, solid-liquid separation should be performed immediately after mixing under the conditions of a phosphorus to total iron molar ratio of 0.20:1 to 0.40:1, a temperature of 20°C to 35°C, and a time of 20 min to 60 min. This will result in a liquid phase with a clear sampling point and better detection repeatability. Only samples with an increase in the free citric acid ratio within the range of 8 to 25 percentage points were considered to meet the response range.
[0119] Further investigation into the concentration of ferric sulfate solution, reaction temperature, and reaction time revealed that when the concentration of ferric iron in the ferric sulfate solution was below 0.15 mol / L, the volume of a single batch of reaction solution increased significantly, prolonging the time required for subsequent acid ripening and filtration. When the concentration of ferric iron was above 0.35 mol / L, the dissolution time of ferric sulfate increased, and persistent turbidity was more likely to occur during the addition of the first portion of citric acid. Therefore, controlling the concentration of ferric iron between 0.15 mol / L and 0.35 mol / L is beneficial for balancing ferric sulfate dissolution, reaction uniformity, and equipment processing capacity.
[0120] When the initial reaction temperature is below 25℃, the turbidity of the initial reaction solution decreases slowly after the first portion of citric acid is added, and detectable changes in state are still observed after stirring for 90 minutes. When the initial reaction temperature is above 40℃, the color of the reaction solution deepens, and the amount of precipitate after acidic ripening increases. Therefore, controlling the initial reaction temperature between 25℃ and 40℃, and controlling the stirring time after the first portion of citric acid is added between 30 minutes and 90 minutes, can ensure that the initial reaction solution becomes homogeneous within a reasonable processing time.
[0121] When adding the second portion of citric acid, a temperature below 20°C in the acidification intermediate solution prolongs the time required for the disappearance of speckled suspended matter, while a temperature above 30°C increases localized color changes and subsequent precipitation. When the second portion of citric acid is added for less than 15 minutes, a short-term high-concentration area easily appears near the addition point; after 45 minutes, the turbidity and application effect of the resulting second reaction solution do not show further improvement. Therefore, controlling the temperature of the acidification intermediate solution between 20°C and 30°C, controlling the addition time of the second portion of citric acid between 15 and 45 minutes, and continuing stirring for 20 to 60 minutes after complete addition can balance the uniformity of addition and processing efficiency.
[0122] During the second acidification process, when the sulfuric acid addition time for each stage was less than 15 minutes, the instantaneous temperature rise and local color changes in the reactor increased; when the addition time for each stage exceeded 45 minutes, the product test results did not continue to improve. When stirring for less than 20 minutes after each stage of sulfuric acid addition, the free sulfuric acid concentration at different sampling locations varied significantly before the next stage of sulfuric acid addition; after stirring for more than 45 minutes, the difference in free sulfuric acid concentration at each sampling location did not decrease further. Therefore, controlling the sulfuric acid addition time for each stage to be between 15 and 45 minutes, and continuing stirring for 20 to 45 minutes after each stage of addition, can ensure the uniformity of the second acidification process while avoiding unnecessary extension of the production cycle.
[0123] The above examples and comparative examples demonstrate that this invention, by limiting the total feed ratio of citric acid and ferric iron, divides the citric acid into two parts, and sets up a first acidification between the addition of the two parts of citric acid. Then, the second reaction solution undergoes a second to third stage of second acidification and acid maturation of the original solution, forming a preparation process with clearly defined material dosages, feeding order, acidification endpoint, cumulative pumping time, maturation completion conditions, and post-treatment methods. The examples cover common application scenarios for phosphorus-containing gold tailings, high-calcium, high-acid-consumption gold tailings, and high-iron, aluminum-containing fine-grained gold tailings. Those skilled in the art can complete the preparation and application verification of the recovery agent based on the disclosed parameters and detection methods.
Claims
1. A process for preparing a rare earth metal co-leaching and recovery agent for gold tailings, characterized in that, Includes the following steps: Citric acid, ferric sulfate, and sulfuric acid are prepared, wherein the molar ratio of the total amount of citric acid to the total amount of trivalent iron in the ferric sulfate is 0.60:1 to 0.85:1, and the citric acid is divided into a first part of citric acid and a second part of citric acid. The ferric sulfate is dissolved in water to obtain a ferric sulfate solution; without adding the sulfuric acid, the first portion of citric acid is added and the mixture is stirred to obtain a first reaction solution; Sulfuric acid is added to the first reaction solution for the first acidification, so that the concentration of free sulfuric acid in the acidification intermediate solution is 0.06 mol / L to 0.16 mol / L. Then, the second part of citric acid is added and the reaction is stirred to obtain the second reaction solution. The remaining sulfuric acid required for the second acidification is added to the second reaction solution in two or three stages, with the amount of sulfuric acid added in the later stage not less than the amount added in the earlier stage, until the concentration of free sulfuric acid in the resulting second acidification solution is 0.15 mol / L to 0.50 mol / L; Without adding water or performing solid-liquid separation, the second acidification solution is acidically matured at 20°C to 35°C for 2 to 8 hours. The matured second acidification solution is filtered, and the main filtrate is collected. The amount of water added is determined according to the total iron concentration of the main filtrate, and the total iron concentration is adjusted to 0.10 mol / L to 0.30 mol / L to obtain a rare earth metal synergistic leaching and recovery agent for gold tailings.
2. The preparation process of a rare earth metal synergistic leaching and recovery agent for gold tailings according to claim 1, characterized in that, The concentration of ferric iron in the ferric sulfate solution is from 0.15 mol / L to 0.35 mol / L; The temperature of the ferric sulfate solution is maintained between 25°C and 40°C. After all the first portion of citric acid has been added, the reaction is stirred for 30 to 90 minutes to obtain the first reaction solution.
3. The preparation process of a rare earth metal synergistic leaching and recovery agent for gold tailings according to claim 2, characterized in that, The sulfuric acid required for the first acidification is added to the first reaction solution, and the cumulative pumping time of the sulfuric acid is 15 min to 45 min. Continue stirring until the concentration of free sulfuric acid in the resulting acidified intermediate solution is 0.06 mol / L to 0.16 mol / L. Stop adding sulfuric acid and continue stirring for 20 to 60 minutes before adding the second portion of citric acid.
4. The preparation process of a rare earth metal co-leaching and recovery agent for gold tailings according to claim 3, characterized in that, The temperature of the acidification intermediate solution is maintained at 20°C to 30°C. The second part of citric acid is added to the acidification intermediate solution within 15 min to 45 min. After all the second part of citric acid has been added, the reaction is stirred for another 20 min to 60 min to obtain the second reaction solution.
5. The preparation process of a rare earth metal co-leaching and recovery agent for gold tailings according to claim 3, characterized in that, The remaining sulfuric acid required for the second acidification is divided into two or three stages, and the sulfuric acid in each stage is added to the second reaction solution in sequence. The amount of sulfuric acid added in the latter paragraph is not less than the amount of sulfuric acid added in the former paragraph.
6. The preparation process of a rare earth metal co-leaching and recovery agent for gold tailings according to claim 5, characterized in that, The cumulative pumping time of sulfuric acid in each segment is 15 min to 45 min. After the cumulative pumping of sulfuric acid in each segment is completed, an inter-segment acidification balance is carried out for 20 min to 45 min before adding the sulfuric acid in the next segment. After all the remaining sulfuric acid has been added, the concentration of free sulfuric acid in the resulting second acidification solution is 0.15 mol / L to 0.50 mol / L.
7. The preparation process of a rare earth metal co-leaching and recovery agent for gold tailings according to claim 6, characterized in that, After all the remaining sulfuric acid has been added, the second acidified solution is subjected to acidic aging at 20°C to 35°C for 2 to 8 hours without adding water or performing solid-liquid separation.
8. The preparation process of a rare earth metal co-leaching and recovery agent for gold tailings according to claim 7, characterized in that, After the acidic ripening is completed, the second acidified solution is filtered, and the total iron concentration is adjusted to 0.10 mol / L to 0.30 mol / L by adding water. The filtrate obtained from the filtration is collected to obtain the gold tailings rare earth metal co-leaching and recovery agent. The free citric acid in the gold tailings rare earth metal co-leaching recovery agent accounts for 15% to 35% of the total citric acid.
9. The preparation process of a rare earth metal co-leaching and recovery agent for gold tailings according to claim 8, characterized in that, A sample was taken from the rare earth metal co-leaching and recovery agent of the gold tailings as a response sample. Potassium dihydrogen phosphate was added to the response sample according to the molar ratio of phosphorus to total iron in the response sample of 0.20:1 to 0.40:
1. The mixture was mixed at 20°C to 35°C for 20 min to 60 min, and then solid-liquid separation was performed. After solid-liquid separation, the proportion of free citric acid in the resulting liquid phase is 8 to 25 percentage points higher than that before the addition of potassium dihydrogen phosphate. The free citric acid ratio is the ratio of the amount of free citric acid to the total amount of citric acid.